Association of anemia with BMI in paramedical students of the remote and rural high land of Mid-Western Nepal - Pokhrel, Bishal; Parajuli, Kirti; Nayak, Ramesh; Subedi, Dharma Datta (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: Anemia is a widespread public health issue. It impairs immune systems and is linked to an increase in morbidity. Additional factors linked to lower hemoglobin (Hb) levels in adolescents include lack of awareness, low educational status, poor dietary practices, and unhealthy eating habits, low iron bioavailability of the diet, decreased physical activity, malaria, and parasite infestations. Studies on the incidence and severity of anemia among Nepali college students are extremely rare. The significance of research on the prevalence of anemia among college students cannot be underestimated. The study's objective was to evaluate the relationship between anemia and BMI in paramedical students from the isolated, rural highlands of Midwestern Nepal. Materials and Methods: A quantitative cross-sectional study was conducted among the paramedical students of KAHS. A total of 96 students from paramedical students were participated in this study. Before collecting the data, the consent was taken from students. Data were collected from a semi-structured questionnaire and analyze by using SPSS software (20.0 Version). A chi square test was used to show the relationship between demographic variables and anemia. Results: The prevalence of anemia was 20.8% (male=6.1% and female=53.3%) among the 96 students. There was no significant association between anemia and BMI (P>0.05). Conclusion: The anemic status of students was significantly associated with gender but BMI and age where not the factors of anemic status in this Therefore, there should be adequate diet and nutritional status needs to be emphasized for paramedical students who are well educated and well oriented about nutrition and its ill effect on health.